Exploring with a magnifying glass - Rainis, Kenneth G. (New York : Watts, 1991)
Presents activities using a magnifying glass and, for the most part, objects that are found around the house.
Includes bibliographical references and index.
Elem. School Library Collection.
School Library Journal.
7-10.
Young Adult
Keywords: Magnifying glasses -- Experiments -- Juvenile literature; Science -- Experiments -- Juvenile literature; Experiments; Magnifying glasses -- Experiments; Science -- Experiments; Magnifying glasses -- Experiments; Science -- Experiments